An Analysis Translation Slang Language Based on TikTok Content at The Fifth Semester Students of English Education Department Universitas Islam Madura - Sa'adah, Khalifatus; Yunitaka Bahrudin, Dinar Vincy; Jaftiyatur Rohaniyah (Institut Agama Islam Negeri Palopo, 2025)
This study aims to analyze the strategy of translating English slang based on TikTok content by fifth semester students of English Education Department Universitas Islam Madura. Using a qualitative case study approach, data were collected through a translation worksheet and semi-structured interviews with 23 students. Ten slang words from TikTok were chosen as translation material. The results showed that the most dominant strategy used was equivalence, where students tended to choose the appropriate meaning in the target culture, such as translating